Prenatal diagnosis of the VACTERL association using routine ultrasound examination. Issue 10 (2nd June 2015) - Debost‐Legrand, Anne; Goumy, Carole; Laurichesse‐Delmas, Hélène; Déchelotte, Pierre; Perthus, Isabelle; Francannet, Christine; Lémery, Didier; Gallot, Denis
<x xml:space="preserve">Abstract</x> Background The prognosis and early neonatal management of the VACTERL association depend mainly on the severity of malformations ascertained prenatally. Methods Here we reviewed the spectrum of clinical features observed in cases of VACTERL association ascertained prenatally through ultrasound examination but examined at birth and compared them with cases ascertained postnatally. Results From 1995 to 2011, a total of 19 cases of VACTERL association were observed in our center; 10 were ascertained prenatally and confirmed after birth whereas 9 were ascertained only after birth. The types and frequencies of malformations observed prenatally were as follows: renal malformations (45%), tracheoesophageal fistula (44%), cardiac malformations (20%), vertebral (13%), and limb (11%) defects. Anal atresia was never detected using routine prenatal ultrasound examination. Conclusion Further studies of fetuses with the VACTERL association are necessary to better delineate the malformations spectrum observed prenatally to improve the early recognition of the VACTERL association. Birth Defects Research (Part A) 103:880–886, 2015. © 2015 Wiley Periodicals, Inc.